Asian North American identities : beyond the hyphen - Ty, Eleanor Rose, 1958-; Goellnicht, Donald C., 1953-2019 (Indiana University Press, 2004)
The nine essays in Asian North American Identities explore how Asian North Americans are no longer caught between worlds of the old and the new, the east and the west, and the south and the north. Moving beyond national and diasporic models of ethnic identity to focus on the individual feelings and experiences of those who are not part of a dominant white majority, the essays collected here draw from a wide range of sources, including novels, art, photography, poetry, cinema, theatre, and popular culture.